Soil Respiration Characteristics and Influencing Factors of Shrub Ecosystem on the Loess Plateau - ZHANG Kuiyue; LIU Dengfeng; LIU Hui; ZHAO Xiaoyu; GUO Fengnian; MENG Xianmeng; HUANG Qiang (Renmin Zhujiang)
Soil respiration is one of the main sources of atmospheric carbon.In recent years,the vegetation cover of the Loess Plateau has changed significantly.To explore the change rules and influencing factors of soil respiration in the shrub ecosystem,this paper used the infrared gas analyzer to observe the soil respiration rate at three measuring points of the Chunhua shrub ecosystem in the gully region of the Loess Plateau in 2020,including the bare land and the surface with retained vegetation at different elevations.The results show the following:① the diurnal soil respiration rate in the Chunhua shrub ecosystem shows a single-peak curve.The soil respiration rate of the land with preserved vegetation is always higher than that of the bare land within 1 day.② There is a significant positive correlation between diurnal soil respiration rate and soil temperature,which could explain 83% of the diurnal variation of soil respiration rate.The diurnal variation of soil respiration rate of shrub ecosystem in gully region of Loess Plateau is negatively correlated with soil moisture.③ The diurnal variation of soil respiration rate,soil temperature,and soil moisture fluctuates greatly.There is a significant positive correlation between monthly soil respiration rate and soil temperature in the gully region of the shrub ecosystem.